THE CONCEPT AND GOALS OF THE ECONOMETRICS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
We will discuss the fundamental principles and methods of econometrics, as well as the various models and methods used to analyse data sets. We will also look at how estimators estimate economic model parameters in econometric analysis. Finally, we’ll give real-world examples of econometrics’ success. Econometrics helps economists analyse complex variables and make data-driven decisions. It uses statistical methods to analyse economic data, estimate parameters, test theories, and predict events.